1999
DOI: 10.5191/jiaee.1999.06102
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Extension Agents Regarding Sustainable Agriculture in the Khorasan Province, Iran

Abstract: As Iran addresses the goal of self-sufficiency in the production of food and fiber products, sustainable agriculture is gaining interest within Extension and the Ministry of Agriculture as a means of achieving this goal. Dependence on pesticide and insecticide imports, compounded by a growing population, limited arable land, and high soil erosion, has led to the call for more appropriate agricultural practice. Little is known, however, about extension agents= perceptions regarding sustainable agriculture pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
4
6
0
1
Order By: Relevance
“…This result is similar to previous findings that extension agents in the Philippines tend to have a positive attitude toward organic agriculture [52,53]. In this context, previous studies also reported a moderate level of EA's perception regarding dimensions of organic agriculture namely; social responsibility; economic viability; production efficiency, and environmental sustainability [54][55][56].…”
Section: Discussionsupporting
confidence: 90%
“…This result is similar to previous findings that extension agents in the Philippines tend to have a positive attitude toward organic agriculture [52,53]. In this context, previous studies also reported a moderate level of EA's perception regarding dimensions of organic agriculture namely; social responsibility; economic viability; production efficiency, and environmental sustainability [54][55][56].…”
Section: Discussionsupporting
confidence: 90%
“…The main purpose of this study was to determine attitudes of extension workers towards SAP concepts and results revealed that extension workers attitudes towarsd dimension of SAP is favorable. This finding confirms the results of previous research (Chizari et al, 1999;Minarovic and Mueller, 2000;Straquadine, 1997; Science Publications AJES Allahyari et al, 2008;Allahyari, 2008;Udoto and Flowers, 2001;Williams and Wise, 1997). Among four dimensions of SAP namley; production efficency, social responsibility, environmnetal sustainability and economic viability, extension workers ranked social responsibility as hightest rank folowed by production efficency, economic viability and environmnetal sustainability.…”
Section: Discussionsupporting
confidence: 89%
“…Hence the first step to identify major obstacles to adoption of sustainable agricultural practices in Malaysia is to examine extension services to find out to what extent the extension workers acquired positive attitudes on sustainable agriculture? Past researches have been conducted to determine extension workers' attitude towards SAP (Chizari et al, 1999;Minarovic and Mueller, 2000;Straquadine, 1997;Allahyari et al, 2008;Allahyari, 2008;Udoto and Flowers, 2001;Williams and Wise, 1997). Scholars argued that generating desirable change in the attitude of extension workers at first step can be used as a foundation for extension workers to transfer SAP to the farmers.…”
Section: Introductionmentioning
confidence: 99%
“…A distinct strain of literature from the field of extension studies has demonstrated the importance of extension agents' perceptions and attitudes towards conservation technologies in spurring their adoption among farmers (e.g., Wallace, 1999;Chizari, Lindner, and Zoghie, 1999;Jayaratne, Gaskin, Lee, Reeves, & Hawkins, 2007). A second and even larger literature has focused on the other half of the equation the socioeconomic context and decisionmaking behavior of farmers.…”
Section: Introductionmentioning
confidence: 99%